2014
DOI: 10.2298/bah1402339l
|View full text |Cite
|
Sign up to set email alerts
|

The effect of starter dosage and fermentation time on pH and lactic acid production

Abstract: The aim of this research is to observed the effect of starter dosage and fermentation time on pH and lactic acid production. This study used Completely Randomized Design (CRD) factorial pattern 5 x 3. The first factor is starter dosage and the second factor is fermentation time. Kefir samples were prepared using of 5, 10, 15, 20 and 25% (v/v) kefir grains, with three fermentation time 8, 16 and 24 hours. Results indicated that kefir with 10% starter and 16 hours fermentation time give the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
9
1
5
Order By: Relevance
“…This is due to the decreasing pH value caused by the increased number of lactic acids produced from the conversion of lactose into lactic acid. Lengkey & Balia (2014) suggested that the best kefir could be produced by the addition of 10% kefir grain with 16 hours incubation period and the acidity of 1.476%.…”
Section: Percentage Of Lactic Acid In Goat-milk Kefirmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the decreasing pH value caused by the increased number of lactic acids produced from the conversion of lactose into lactic acid. Lengkey & Balia (2014) suggested that the best kefir could be produced by the addition of 10% kefir grain with 16 hours incubation period and the acidity of 1.476%.…”
Section: Percentage Of Lactic Acid In Goat-milk Kefirmentioning
confidence: 99%
“…Purnomo & Muslimin (2012) found the best kefir with an addition of 7% kefir grain with 24 hours incubation, producing a pH of 4.63 and 0.73% lactic acid percentage, 0.92% ethanol, and the best goat-milk kefir with the addition of 7% kefir grain for 24 hours incubation time. The characteristics of kefir depend on the duration of fermentation (Lengkey & Balia, 2014), the medium used (Lengkey, 2002), fermentation temperature (Setyawardani et al, 2014), and the ratio of kefir grain with milk (Agustina et al, 2013); (Lengkey et al, 2013). Sulmiyati et al (2018 b ) reported the type of bacteria, temperature, duration of fermentation, and the type of milk were used as the parameters to characterize kefir.…”
Section: Introductionmentioning
confidence: 99%
“…Purnomo and Muslimin (2012) reported that the pH of goat milk kefir with the addition of 3% kefir grains (w/w) decreased along with 0 hour of incubation time (control), the pH was 6.17±0.01; at 18 hours of incubation the pH was 4.91±0.01; at 21 hours of incubation the pH was 4.83±0.02; and at 24 hours of incubation the pH was 4.77±0.02 respectively. Lengkey and Balia (2014) reported that kefir pH value with the addition of 5% kefir grains with an incubation time of 8 hours was 4.6; 16 hours was 4.5 and 24 hours was 4.3. According to Adesokan et al (2011) the pH value was strongly related to the produced acid content.…”
Section: Resultsmentioning
confidence: 99%
“…Purnomo and Muslimin (2012), reported that the acidity of goat milk kefir on the addition of kefir grains 3% (w/w), the increase acidity based incubation time, at the incubation time of 0 hours was 0.41±0.02%; 18 hours was 0.51±0.1; 21 hours was 0.61±0.01 and 24 hours was 0.70±0.01 while the pH value obtained was 6.17±0.01; 18 hours was 4.91±0.01; 21 hours was 4.83±0.02; and 24 hours was 4.77±0.02. Lengkey and Balia (2014) described that production of lactic acid after 5% kefir grains addition with an incubation time of 8 hours was 0.37%; 16 hours was 1.10%, and 24 hours was 1.24%. Suriasih et al (2012) stated that the acidity level of cow's milk kefir at a concentration of 5% (w/v) with an incubation time for 24 hours was 0.89±0.03; for 48 hours was 1.28±0.04 and 72 hours of incubation time was 1.73±0.02.…”
Section: The Lactic Acid Concentration Of Goat Milk Kefirmentioning
confidence: 99%
“…Hal ini menunjukkan pada lama pemeraman 28 hari memberikan kesempatan yang optimal pada mikroba untuk mendegradasi lignoselulosa dan lignohemiselulosa, terlepasnya selulosa dan hemiselulosa dari lignin menjadi bentuk yang mudah larut dan dapat dimanfaatkan sebagai sumber energi bagi mikroba sehingga terjadi penurunan kandungan serat kasar dan fraksi serat. Hasil fermentasi sangat dipengaruhi lama pemeraman karena berhubungan dengan aktivitas mikroba (Lengkey and Balia 2014). Waktu yang optimal bagi mikroba mendegradasi substrat adalah 4 minggu (Surono et al, 2012).…”
Section: Kandungan Nutrisi Jerami Jagungunclassified